Characterization of High-Flux CdZnTe with optimized electrodes for 4th generation synchrotrons. (1st November 2022) - Baussens, O.; Ponchut, C.; Ruat, M.; Bettelli, M.; Zanettini, S.; Zappettini, A.
Abstract: In this collaboration work between IMEM-CNR and the ESRF, we explore the potential of the Redlen Technologies High-Flux Cadmium Zinc Telluride (HF-CZT) material for direct X-ray detection at fluxes ranging from 10 +7 to 10 +12 photons mm −2 s −1 . HF-CZT single crystals with optimized electroless gold and sputtered platinum electrodes are characterized both under dark conditions and under X-ray irradiation. We report low leakage current under dark conditions (<100 pA/mm 2 at 5 kV/cm). We also report good linearity ( R 2 > 0.999) under moderate to high incident X-ray flux (10 +7 to 10 +10 photons mm −2 s −1 ) as well as good stability and reproducibility for incident X-ray fluxes up to 10 +12 photons mm −2 s −1 . Finally, we study transient phenomena in the seconds time range and report fast stabilization time (<200 ms) and negligible afterglow in this time range.